A Non-invasive Wearable Neck-cuff System for Real-time Sleep Monitoring - Bittner, Ray; Blank, Tom; Saw, Nick; Rofouei, Mahsan; Sinclair, Mike; DeJean, Gerald; Heffron, Jeff (IEEE Computer Society, 2011)
Sleep is an important part of our lives which affects many life factors such as memory, learning, metabolism and the immune system. Researchers have found correlations between sleep and several diseases such as Chronic Obstructive Pulmonary disease, Chronic Heart Failure, Alzheimer’s disease, etc. However, sleep data is mainly recorded and diagnosed in sleep labs or in hospitals for some critical cases with high costs.